Effects of video digitization in pubic arch interference assessment for prostate brachytherapy. - Haberman, K. (IEEE Transactions on information technology in biomedicine)
Recently, it has been shown that prior to surgery a transrectal ultrasound (TRUS) study of the prostate and pubic arch can effectively determine pubic arch interference (PAI), a major stumbling block for the prostate brachytherapy (radioactive seed implantation) procedure. This PAI determination is currently being done with digital images taken directly from an ultrasound (US) machine. However, 70-75% of US machines used in prostate brachytherapy do not have a method to save or transfer digital image data for external use. To allow PAI assessment regardless of US platform and to keep costs to a minimum, we need to digitize the images from the US video output when there is no direct digital transfer capability. D/A and A/D conversions can introduce quantization error and other noises in these digitized images. The purpose of this work is to assess the image degradation caused by digitization and quantitatively evaluate whether after digitization it is still possible to accurately assess PAI. We used a PAI assessment algorithm (developed in previous research by our group) to predict the location of the pubic arch on both digital images and those captured after digitization. These predicted arch locations were compared to the "true" position of the pubic arch as established during surgery. Despite apparent image degradation due to the D/A and A/D conversions, we found no statistically significant difference between the accuracy of the predicted arch locations from the digitized images and those from the digital images. By demonstrating equally accurate determination of pubic arch locations using digital and digitized images, we conclude that TRUS-based PAI assessment can be easily and inexpensively performed in clinics where it is needed.